2024
DOI: 10.3390/ani14040593
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Cleaning and Disinfection Practices on Pig Farms across Ten European Countries

Iryna Makovska,
Ilias Chantziaras,
Nele Caekebeke
et al.

Abstract: This study delves into the assessment of cleaning and disinfection (C&D) measures within the context of European pig farming, employing the Biocheck.UGent™ tool as an effective instrument for evaluation. A comprehensive set of relevant parameters was examined to enable meaningful comparisons across farms from 10 European countries during four years (2019–2022). Findings indicate a notable increase in C&D measure implementation in select countries (Belgium, Finland, Italy, and Spain), reflecting heighte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
(83 reference statements)
0
1
0
Order By: Relevance
“…Despite these limitations, these studies and ours show that ATP swabbing, although requiring investment by farmers, could be a rapid and useful tool to evaluate effectiveness of hygiene routines on-farm. This is particularly relevant, given that a recent study showed that only 1% of pig farms evaluate hygiene after cleaning and disinfection procedures ( Makovska et al, 2024 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite these limitations, these studies and ours show that ATP swabbing, although requiring investment by farmers, could be a rapid and useful tool to evaluate effectiveness of hygiene routines on-farm. This is particularly relevant, given that a recent study showed that only 1% of pig farms evaluate hygiene after cleaning and disinfection procedures ( Makovska et al, 2024 ).…”
Section: Discussionmentioning
confidence: 99%